Discursive competence strategies to improve english speaking skills in 7th basic year students at Adolfo Jurado González school, Santa Elena - province of Santa Elena, school year 2021-2022 - Merejildo Quimí, Víctor Enrique (2021)
The teaching-learning process of the English language copes with different opinions about what are the best procedures to apply in teaching. Such studies drive teachers to adopt some of them in order to achieve the correct learning in the students. The difficulty to find quality teaching strategies is presented day by day in the four skills of the English language. This work is focused on the importance of discursive competence strategies to enhance the speaking skills. Therefore, the study of such strategies ends up in the use of dramatizations through plays that contribute in the correct development of the speaking area. To carry out this research, it was necessary to study the 7th basic year students at Adolfo Jurado Gonzalez school in order to know the real situation of students directed to the speaking skills. Therefore, the aim of this work is to foster the use of the dramatization to plays as a didactic strategy in which students have the opportunity to perform themselves and create an interactional environment that largely contributes in the improvement of the speaking skills.